Risk of acute myocardial infarction among new users of chondroitin sulfate: A nested case-control study. - Ramón Mazzucchelli; Sara Rodríguez-Martín; Alberto García-Vadillo; Miguel Gil; Antonio Rodríguez-Miguel; Diana Barreira-Hernández; Alberto García-Lledó; Francisco J de Abajo (PLoS ONE, 2021)
Objective To test the hypothesis that the use of chondroitin sulfate (CS) or glucosamine reduces the risk of acute myocardial infarction (AMI). Design Case-control study nested in a primary cohort of patients aged 40 to 99 years, using the database BIFAP during the 2002-2015 study period. From this cohort, we identified incident cases of AMI and randomly selected five controls per case, matched by exact age, gender, and index date. Adjusted odds ratios (AOR) and 95% confidence interval (CI) were computed through a conditional logistic regression. Only new users of CS or glucosamine were considered. Results A total of 23,585 incident cases of AMI and 117,405 controls were included. Of them, 89 cases (0.38%) and 757 controls (0.64%) were current users of CS at index date, yielding an AOR of 0.57 (95%CI: 0.46-0.72). The reduced risk among current users was observed in both short-term (<365 days, AOR = 0.58; 95%CI: 0.45-0.75) and long-term users (>364 days AOR = 0.56; 95%CI:0.36-0.87), in both sexes (men, AOR = 0.52; 95%CI:0.38-0.70; women, AOR = 0.65; 95%CI:0.46-0.91), in individuals over or under 70 years of age (AOR = 0.54; 95%CI:0.38-0.77, and AOR = 0.61; 95%CI:0.45-0.82, respectively) and in individuals at intermediate (AOR = 0.65; 95%CI:0.48-0.91) and high cardiovascular risk (AOR = 0.48; 95%CI:0.27-0.83), but not in those at low risk (AOR = 1.11; 95%CI:0.48-2.56). In contrast, the current use of glucosamine was not associated with either increased or decreased risk of AMI (AOR = 0.86; 95%CI:0.66-1.08). Conclusions Our results support a cardioprotective effect of CS, while glucosamine seems to be neutral. The protection was remarkable among subgroups at high cardiovascular risk.